Nonverbal Behavior in Selection Interviews: Relation to Communion, Agency, and Interview Performance - Tescari, Marie-Eve; Bangerter, Adrian (My University, 2024)
Abstract: In selection interviews, applicant nonverbal cues elicit impressions that affect evaluations. However, little is known about which micro cues and macro impressions are impactful. The current study measured 21 micro and macro impressions and their influence on interview performance from thin slices of 70 videotaped structured mock interviews. Interview performance was positively associated with six macro impressions and with vocal attractiveness. Performance was negatively related to being anxious and facial attractiveness. Micro cues, overall physical appearance, and overall likability were not correlated with performance. Smiling and hand gestures were associated with macro impressions. Moreover, macro impressions combined into the Big Two dimensions of interpersonal perception, Communion and Agency, which both predicted interview performance.